Automated smart car parking system for smart cities demand employs internet of things technology - Rahman Atiqur (Institute of Advanced Engineering and Science, 2021)
The use of smart cities rises quickly with the fast progress of the Internet of Things (IoT) advances. The smart city idea essentially getting city life; as well raises the capability of municipal jobs and facilities plus form viable economic progress of the city. The point of convergence of this paper is to introduce an automated smart automobile parking system for smart cities demand employs internet of things (IoT) technology. The offered automobile parking system covers an IoT entity sent nearby for getting sorted out the existing parking spots which are quicker contrasted with different frameworks. It is a viewpoint gave as an iOS application for reservation, entrance, supervision, and leaving the car park places.